Prognostic role of 11C‐choline PET/CT scan in patients with metastatic castrate resistant prostate cancer undergoing primary docetaxel chemotherapy. Issue 1 (11th October 2021) - Jimbo, Masaya; Andrews, Jack R.; Ahmed, Mohamed E.; Dundar, Ayca; Karnes, R. Jeffrey; Bryce, Alan H.; Kendi, Ayse T.; Kwon, Eugene D.; Lowe, Val J.; Bold, Michael S.
Abstract: Background: We sought to assess the prognostic utility of 11C‐choline positron emission tomography/computed tomography (PET/CT) in patients with metastatic castrate resistant prostate cancer (mCRPC) undergoing primary docetaxel chemotherapy. Methods: We performed a single institution retrospective analysis of 77 mCRPC patients who were treated with 6 cycles of docetaxel chemotherapy, and who also underwent 11C‐choline PET/CT scans at baseline (before chemotherapy), mid‐course (after 3 cycles), and posttherapy (after 6 cycles). We evaluated treatment response based on percent change in blood pool‐corrected maximum standardized uptake value (SUVmax) of the target lesion on PET/CT, as well as percent change in serum prostate specific antigen (PSA). Logistic regression analysis was used to identify factors associated with complete treatment response. Progression free survival (PFS) analysis was performed using log‐rank test and shown on Kaplan–Meier plot. Results: Percent change in blood pool‐corrected SUVmax on mid‐course scan was a significant predictor of complete response (odds ratio [OR]: 0.98, 95% confidence interval [CI]: 0.96–0.99, p = .0003), whereas percent change in PSA was not (OR: 0.99, 95% CI: 0.99–1.01, p = .6025). 57 of 77 patients (74%) achieved ≥20% reduction in blood pool‐corrected SUVmax on mid‐course; these patients were 3.6 times more likely to achieve complete response after full 6 cycles of docetaxel chemotherapy, compared to patients with <20% reduction in blood pool‐corrected SUVmax (OR: 3.56, 95% CI: 1.04–16.52, p = .0420). Median PFS in the complete response group was 35.1 months (95% CI: 26.0–52.7 months), compared to 9.4 months (95% CI: 6.9–13.0 months) in the incomplete response group ( p = .0005). Conclusions: Our study showed that mid‐course and posttherapy 11C‐choline PET/CT evaluation for mCRPC patients undergoing primary docetaxel chemotherapy can predict full course treatment response and PFS, respectively. 11C‐choline PET/CT imaging may provide valuable prognostic information to guide treatment choices for patients with mCRPC.